Auto‐thermal chemical looping combustion of sulphur with Fe2O3 oxygen carriers for sulphuric acid production: Thermodynamics. (17th November 2022) - Gao, Peng; Shen, Yue; Zheng, Min; Bao, Guirong; Wang, Hua; Xie, Haitao; Wang, Lulu
Abstract: Chemical looping is a novel fuel conversion and material separation technology. It can be applied to obtain sulphur through selective oxidation of H2 S. Further, chemical looping combustion (CLC) of sulphur can generate SO2 with a high concentration without NOx formation. The high SO2 concentration is adjustable and facilitates large‐scale H2 SO4 production. In this study, we examined the thermodynamics of the CLC of sulphur for H2 SO4 production, which has not been reported previously. We analyzed the effects of reactor temperature and sulphur to Fe2 O3 oxygen carrier (OC) ratios on sulphur allotrope transformations and on the distributions of reaction products. Moreover, the reactors were operated auto‐thermally. Based on this design, we examined the effects of fuel reactor (FR) and air reactor temperatures on the minimum recirculation of the OC, as well as the gas and solid products and heat released from the air reactor. Our results showed that the CLC of sulphur with Fe2 O3 OC could occur through an auto‐thermal process. The FR in a sulphur CLC system should be operated over a temperature range of 800–950°C, with an Fe2 O3 OC recirculation between 45 and 143 kg/kgS(s) . Furthermore, when the FR was operated in the auto‐thermal mode, we achieved 100% SO2 conversion. The findings of this study may be applied to reactor design for large‐scale H2 SO4 production through CLC of sulphur.